Model-based total evidence phylogeny of Neotropical electric knifefishes (Teleostei, Gymnotiformes) - Tagliacollo, Victor A. [UNESP]; Bernt, Maxwell J.; Craig, Jack M.; Oliveira, Claudio [UNESP]; Albert, James S. (Elsevier, 2016)
This study provides the most comprehensive Model-Based Total Evidence (MBTE) phylogenetic analyses of the clade Gymnotiformes to date, reappraising relationships using a dataset comprised of six genes (5277 bp) and 223 morphological characters, and an ingroup taxon sample including 120 of 212 valid species representing 34 of the 35 extant genera. Our MBTE analyses indicate the two main gymnotiform clades are Gymnotidae and Sternopygoidei, the latter comprised of Rhamphichthyoidea (Rhamphichthyidae + Hypopomidae) and Sinusoidea (Sternopygidae + Apteronotidae). Within Gymnotidae, Electrophorus and Gymnotus are sister taxa, and Gymnotus includes the following six clades: (i) G. pantherinus clade, (ii) G. coatesi clade, (iii) G. anguillaris clade, (iv) G. tigre clade, (v) G. cylindricus clade, and (vi) G. carapo clade. Within Rhamphichthyoidea, Steatogenae (Steatogenys + Hypopygus) is a member of Rhamphichthyidae, and Hypopomidae includes the following clades: (i) Akawaio, (ii) Hypopomus, (iii) Microsternarchini, and (iv) Brachyhypopomus. Within Sternopygidae, Sternopygus and Eigenmanninae are sister groups, Rhabdolichops is the sister to other Eigenmanninae, Archolaemus+. Distocyclus is the sister to Eigenmannia, and Japigny is nested within Eigenmannia. Within Apteronotidae, Sternarchorhamphinae (Sternarchorhamphus + Orthosternarchus) is the sister to Apteronotinae, Adontosternarchus is the sister group to other Apteronotinae, Sternarchorhynchini (Sternarchorhynchus + Platyurosternarchus) is the sister to Navajini, and species assigned to Apteronotus are members of two separate clades: (i) A. sensu stricto in the Apteronotini, and (ii) the A. bonapartii clade in the Navajini.
Keywords: Electric fishes; Freshwater fishes; Molecular systematics; Morphological characters; South America; Tropical biodiversity